2023
DOI: 10.1111/btp.13226
|View full text |Cite
|
Sign up to set email alerts
|

Out of steady state: Tracking canopy gap dynamics across Brazilian Amazon

Abstract: Canopy gaps are evidence of disturbances on forest landscapes. A forest stand is in constant flux, with long stretches of biomass accumulation punctuated by episodic disturbances. We used multitemporal airborne laser scanning data to compare the gap dynamics of four Amazon forest sites. We assessed gap dynamics over 1.9–3.8 years between 2017 and 2020 at sites in the central, central eastern, southeastern, and northeastern regions of the Brazilian Amazon, over areas ranging from 590 to 1205 ha at each site. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…Specifically, we did not detect a signal towards more open forests, such as expected for many ecosystems under global change (McDowell et al, 2020), but rather found indications of a densification of forests in our study system. This is well in line with terrestrial observations from earlier studies both in BGNP , in the Alps more broadly (Kulakowski et al, 2017), and was also reported for other systems (Gorgens et al, 2023;Rodes-Blanco et al, 2023). Nonetheless, emerging novel disturbance regimes and ecological responses will likely continue to alter ecosystem dynamics (Seidl, & Turner, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, we did not detect a signal towards more open forests, such as expected for many ecosystems under global change (McDowell et al, 2020), but rather found indications of a densification of forests in our study system. This is well in line with terrestrial observations from earlier studies both in BGNP , in the Alps more broadly (Kulakowski et al, 2017), and was also reported for other systems (Gorgens et al, 2023;Rodes-Blanco et al, 2023). Nonetheless, emerging novel disturbance regimes and ecological responses will likely continue to alter ecosystem dynamics (Seidl, & Turner, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…Once a gap is created, the course for the surrounding forests is set for the coming years, as new gaps are more likely to emerge next to existing gaps, and as gaps keep growing over multiple years. This pattern of spatial dependence was found also in other studies in temperate (Blackburn et al, 2014;Senf, Campbell, et al, 2017), tropical (Gorgens et al, 2023) and boreal forests (Hytteborn & Verwijst, 2014;Vepakomma et al, 2012). Potential processes contributing to the contagious nature of canopy gaps are edge effects (Hunter et al, 2015;Pöpperl & Seidl, 2021), as edge trees are more susceptible to drought and wind (Buras et al, 2018;Seidl et al, 2014); but also dispersal mechanisms, such as the flight of bark beetles, which can contribute to spatially clustered canopy openings (Kautz et al, 2011;Seidl et al, 2016;Senf, Campbell, et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As previously reported, these severities accounted for decadal changes in floristic composition [1,62,103], biomass stock and balance [2,4], organic soil carbon stocks [104], and insect diversity [105,106] in other Central and Northwestern Amazon forests affected by windthrows. Future investigations are needed to improve the remote detection of smaller canopy disturbances across local-to-regional variations in topography, climate, soils, and forest attributes [42][43][44]107].…”
Section: Relating Satellite Data and Field Datamentioning
confidence: 99%
“…In addition to optical satellites, other approaches such as SAR (Synthetic-Aperture Radar [39,40]), LiDAR [41][42][43] and aerial photos [44] have been tested to estimate treemortality associated with windthrows. SAR offers data that are less dependent on weather effects and with spatial resolutions comparable to high-and medium-resolution satellites [45,46].…”
Section: Introductionmentioning
confidence: 99%